Electrolyte and semi-solid-state battery
By using low HOMO energy level solvents and functional additives in the electrolyte, the problem of lithium-rich manganese-based positive electrode materials being easily oxidized and decomposed under high voltage is solved, forming high entropy SEI, suppressing side reactions, and improving the stability and power of the battery performance.
Patent Information
- Application Number
- CN202411258619.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-09
AI Technical Summary
Lithium-rich manganese-based positive electrode material can easily lead to the oxidation and decomposition of the electrolyte at high voltage, and side reactions seriously affect the performance and safety of the battery. The material is highly alkaline and easy to absorb water, resulting in a decline in battery performance and poor power performance.
Use low HOMO energy level solvents such as 2,2,2-trifluoroethanol TFEA, combined with acid and water removal additives such as tris(trimethylsilane) phosphate TMSP and tris(trimethylsilane) borate TMSB, fluorobenzene Infiltrating additives like fluorobenzene FB, and film-forming additives such as lithium difluorodioxalate phosphate LiODFP form high entropy SEI, inhibit side reactions and improve electrode interface stability.
It improves the stability and cycle life of the battery at high voltage, reduces the side reaction of electrolyte, enhances the rate performance and high-temperature storage capabilities, and improves the overall performance of the battery.
Smart Images

Figure CN119253065A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to an electrolyte and a semi-solid battery. Background Art
[0002] Solid-state batteries have attracted much attention due to their higher energy density and stronger thermal stability than traditional liquid lithium-ion batteries. As a phased achievement in the transition from traditional liquid batteries to all-solid-state batteries, semi-solid-state batteries have the advantages of both solid-state batteries and liquid batteries, which has led to relevant scientific research units investing a lot of resources in the research and development of semi-solid-state batteries. At the same time, because the manufacturing process of semi-solid-state batteries is similar to that of existing liquid batteries, their production equipment is compatible with existing liquid battery production equipment. Therefore, semi-solid-state battery technology is expected to be commercialized in a relatively short period of time, while also enabling lithium-ion battery performance to be taken to a higher level.
[0003] The key material technologies of semi-solid batteries include the development of positive electrode materials, negative electrode materials, diaphragm materials and electrolyte materials. As the "blood" of the battery, the electrolyte material is responsible for transferring ions between the positive and negative electrodes. Since the electrolyte is in direct contact with the positive and negative electrodes, it is required that the electrolyte has good compatibility with both the positive and negative electrode materials, has a wide chemical stability window, and can also form an effective SEI on the surface of the positive and negative electrodes. Therefore, the electrolyte needs to be adjusted according to the electrode materials, battery characteristics and battery performance requirements.
[0004] At present, in the field of semi-solid batteries, lithium-rich manganese-based positive electrode materials are receiving great attention due to their characteristics. The lithium-rich manganese positive electrode has a high working voltage and a discharge capacity of up to 300mAh, which can greatly improve the energy density of the battery. Lithium-rich manganese materials mainly use manganese metal, which is cheaper than cobalt and nickel, and can reduce the cost of battery materials. However, lithium-rich manganese materials also face some problems that need to be solved urgently. First, the ultra-high working voltage of lithium-rich manganese also hinders its application. The upper cut-off voltage of lithium-rich manganese batteries can reach 4.6V, and the steady-point voltage window of conventional battery electrolytes is between 2.0-4.3V. Excessive voltage will cause the electrolyte to undergo side reactions such as oxidation and decomposition on the positive electrode side, resulting in gas production in the battery, which seriously affects the battery performance and safety. Secondly, lithium-rich manganese materials are highly alkaline and easily absorb water. They have relatively harsh requirements on the conditions of the battery production site, and excessive water will also lead to a decrease in battery performance. Finally, both lithium-rich manganese materials and solid electrolyte materials have the weakness of low ionic conductivity. The power performance of lithium-rich manganese semi-solid batteries formed by the combination of the two is poor. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an electrolyte and a semi-solid battery.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] An electrolyte comprises a lithium salt, a solvent and an additive; the additive comprises a solvent additive; the solvent additive comprises a low HOMO energy level solvent; preferably, the low HOMO energy level solvent is 2,2,2-trifluoroethanol (TFEA).
[0008] The mass proportion of the low HOMO energy level solvent in the electrolyte is 2-8%, preferably 8%.
[0009] The solvent additives also include acid and water removal additives;
[0010] Preferably, the acid and water removal additive includes one or a mixture of tris(trimethylsilyl)phosphate TMSP or tris(trimethylsilyl)borate TMSB;
[0011] Preferably, the acid and water removal additive accounts for 0.5-0.8% by mass in the electrolyte.
[0012] The acid and water removal additive is a mixture of tris(trimethylsilyl)phosphate TMSP and tris(trimethylsilyl)borate TMSB; preferably, the mass ratio of the two is 3:(3-5).
[0013] The solvent additive also includes a fluorobenzene wetting additive; preferably, the fluorobenzene wetting additive is fluorobenzene FB;
[0014] Preferably, the mass proportion of the fluorobenzene wetting additive in the electrolyte is 0.5-2%, preferably 1%.
[0015] The additives also include film-forming additives; preferably, the film-forming additive is lithium difluorobis(oxalate)phosphate LiODFP;
[0016] Preferably, the mass proportion of the lithium difluorobis(oxalate)phosphate LiODFP in the electrolyte is 0.2-1%, preferably 0.5%.
[0017] The solvent includes one or a mixture of carbonates, sulfates, sulfonates, fluoroesters, fluorosulfates, or fluorosulfonates;
[0018] Preferably, the solvent includes one of propylene carbonate PC, ethylene carbonate EC, vinylene carbonate VC, ethyl methyl carbonate EMC, dimethyl carbonate DMC, diethyl carbonate DEC, fluoroethylene carbonate FEC, propylene sulfite PS, vinyl sulfate DTD, propenyl-1,3-sultone PST, and methylene methane disulfonate MMDS, or a mixture thereof;
[0019] Preferably, the solvent is a mixture of propylene carbonate PC, ethyl methyl carbonate EMC, fluoroethylene carbonate FEC, and vinyl sulfate DTD;
[0020] Preferably, the mass ratio of propylene carbonate PC, ethyl methyl carbonate EMC, fluoroethylene carbonate FEC and vinyl sulfate DTD in the electrolyte is: 6: (61.5-69.8): (5-8): 1.
[0021] The lithium salt is one or a mixture of LiPF6, LiBOB, LiBF4, LiODFB, LiTFSI, LiFSI, LiPO2F2, and LiFOP;
[0022] Preferably, the lithium salt is a mixture of LiPF6, LiFSI and LiPO2F2; preferably, the mass ratio of LiPF6, LiFSI and LiPO2F2 is 10:2:1.2.
[0023] The present invention also includes a semi-solid battery, comprising the electrolyte.
[0024] The semi-solid battery comprises an electrolyte, a positive electrode sheet, a negative electrode sheet and a separator; the positive electrode active material in the positive electrode sheet is a lithium-rich manganese-based positive electrode material coated with a solid electrolyte.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The electrolyte of the present application, by adopting a solvent additive with a low HOMO energy level and optionally combining functional additives (acid and water removal and additives, fluorobenzene wetting additives, film-forming additives) to effectively improve the stability of the battery under high voltage, protect the electrolyte-electrode interface, inhibit the dissolution of transition metals, reduce electrolyte side reactions caused by water, free acid and transition metals, improve the performance of the battery in high-temperature storage tests, and at the same time improve the cycle life and rate performance of the battery.
[0027] 1. Adding solvent additives with low HOMO energy levels can enhance the antioxidant properties of the electrolyte, thereby improving the performance of the battery at high voltage.
[0028] 2. Add acid and water removal additives to reduce the water and free acid content in the battery system due to alkaline residues in the positive electrode, and improve the overall performance of the battery. As a preferred form, a mixed solution of TMSP and TMSB is adopted. The two silane additives work together with lithium salts and solvent additives with low HOMO energy levels to form a high entropy SEI on the negative electrode surface, producing a cocktail effect, which can protect the electrode while reducing the interface impedance.
[0029] 3. Introduce fluorobenzene wetting additives. This additive has a low surface tension and can effectively reduce the electrolyte infiltration time, enhance the contact between solid electrolytes and between solid electrolytes and electrodes, reduce interface resistance, and improve battery rate performance. Adding fluorobenzene wetting additives can also reduce the amount of battery injection and further increase the battery energy density.
[0030] 4. In order to cope with the more active characteristics of lithium-rich manganese-based positive electrode materials, a film-forming additive LiODFP is added. This additive can effectively form a film on the surface of the positive and negative electrodes, inhibit the dissolution and migration of transition metals on the positive electrode side, and improve the cycle life and high-temperature storage performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 HOMO energy level diagram of the solvents and solvent additives of the embodiments and comparative examples of the present invention;
[0032] Figure 2 The figure is a graph showing the rate performance test results of the embodiments of the present invention and the comparative examples;
[0033] Figure 3 The graphs are the cycle performance results of the embodiments of the present invention and the comparative examples;
[0034] Figure 4 It is a result diagram of high temperature storage thickness expansion rate of the embodiment of the present invention and the comparative example;
[0035] Figure 5 It is a result diagram of the negative electrode Mn content of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.
[0037] Embodiment 1:
[0038] A semi-solid battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte;
[0039] The positive electrode sheet is prepared in the following manner: a solid electrolyte-coated lithium-manganese-rich positive electrode material, a conductive agent SuperP, a binder PVDF and N-methylpyrrolidone (NMP) are uniformly mixed in a mass ratio of 96:2.0:2.0 to form a positive electrode slurry; the positive electrode slurry is uniformly coated on the positive electrode collector with a coating amount of 0.018 g / cm2, and then dried at 85°C and cold pressed; after slicing, trimming and striping, the pole ears are welded to form a lithium-ion secondary battery positive electrode sheet.
[0040] The negative electrode sheet is prepared in the following manner: graphite, SiC, conductive agent SuperP, thickener CMC, binder SBR are uniformly mixed with pure water in a mass ratio of 52.5:44:1.0:1.0:1.5 to form a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector copper foil with a coating amount of 0.009g / cm2 and dried at 85°C, and then cold pressed, cut and slit, and the pole ears are welded to form a lithium ion secondary battery negative electrode sheet.
[0041] The separator is a 16μm solid electrolyte coated polyethylene separator.
[0042] The electrolyte includes a lithium salt, a solvent and an additive; the solvent includes one or a mixture of carbonates, sulfates, sulfonates, fluoroesters, fluorosulfates, or fluorosulfonates;
[0043] Preferably, the solvent includes one of propylene carbonate PC, vinyl carbonate EC, vinylene carbonate VC, ethyl methyl carbonate EMC, dimethyl carbonate DMC, diethyl carbonate DEC, fluoroethylene carbonate FEC, propylene sulfite PS, vinyl sulfate DTD, propenyl-1,3-sultone PST, and methylene methanedisulfonate MMDS, or a mixture thereof; preferably, the solvent is a mixture of propylene carbonate PC, ethyl methyl carbonate EMC, fluoroethylene carbonate FEC, and vinyl sulfate DTD; preferably, the mass proportion of propylene carbonate PC, ethyl methyl carbonate EMC, fluoroethylene carbonate FEC, and vinyl sulfate DTD in the electrolyte is: 6:(61.5-69.8):(5-8):1. The lithium salt is one or a mixture of LiPF6, LiBOB, LiBF4, LiODFB, LiTFSI, LiFSI, LiPO2F2, LiFOP; preferably, it is a mixture of LiPF6, LiFSI, LiPO2F2; preferably, the mass ratio of LiPF6, LiFSI, LiPO2F2 in the electrolyte is: 10:2:1.2.
[0044] The additives include solvent additives; the solvent additives include low HOMO energy level solvents; EC, PC, DMC, EMC, DEC, FEC, TFEA were tested, and the results are as follows Figure 1 Therefore, 2,2,2-trifluoroethanol TFEA was used as a low HOMO energy level solvent. The addition amount was tested, as shown in Table 1. The addition of a low HOMO energy level solvent improves the antioxidant properties of the electrolyte, thereby improving the performance of the battery at high voltage.
[0045] The solvent additive also includes an acid-removing and water-removing additive; the acid-removing and water-removing additive includes one or a mixture of tris(trimethylsilyl)phosphate TMSP or tris(trimethylsilyl)borate TMSB; preferably, the mass ratio of the acid-removing and water-removing additive in the electrolyte is 0.5-0.8%. The acid-removing and water-removing additive is a mixture of tris(trimethylsilyl)phosphate TMSP and tris(trimethylsilyl)borate TMSB; preferably, the mass ratio of the two is 3:(3-5). Adding the acid-removing and water-removing additive reduces the content of water and free acid in the battery system due to alkaline residues in the positive electrode, thereby improving the overall performance of the battery (Example 4). Since boron-containing compounds can reduce the internal resistance of the battery, we tested the solution of mixing TMSP and TMSB (Examples 5 and 6). The two silane additives work together with lithium salts and fluorinated solvents to form a high entropy SEI on the surface of the negative electrode, producing a cocktail effect, which can protect the electrode while reducing the interface impedance.
[0046] The solvent additive also includes a fluorobenzene wetting additive; preferably, the fluorobenzene wetting additive is fluorobenzene FB; preferably, the mass proportion of the fluorobenzene wetting additive in the electrolyte is 0.5-2%, preferably 1%.
[0047] The additive has a low surface tension, can effectively reduce the electrolyte infiltration time, enhance the contact between solid electrolytes and between solid electrolytes and electrodes, reduce interface resistance, and improve battery rate performance (Example 7). Adding FB can also reduce the injection volume of the battery, further improving the battery energy density.
[0048] In order to cope with the more active characteristics of lithium-rich manganese-based positive electrode materials, an efficient film-forming additive LiODFP (Example 8) is also added. This additive can effectively form a film on the positive and negative electrode surfaces, inhibit the dissolution and migration of transition metals on the positive electrode side, and improve the cycle life and high-temperature storage performance of the battery.
[0049] The specific embodiment recipe parameters are shown in Table 1.
[0050] Table 1
[0051]
[0052] The positive electrode sheet, negative electrode sheet and separator are assembled into a 12Ah soft-pack laminated battery, and the electrolyte is added to form a semi-solid battery.
[0053] The electrical performance test was carried out on the soft-pack semi-solid full battery, and the results are shown in Table 2.
[0054] Table 2
[0055]
[0056] Figure 2 The rate performance is compared with the discharge capacity under 3C current discharge conditions. Adding LiODFB and FB can effectively improve the rate performance of the battery.
[0057] Figure 3 The results of the room temperature cycle test at 25°C are shown. The cycle format is 1C constant current charging to 4.6V, then constant voltage charging, and the cut-off current is 0.05C. After charging to 100% SOC, it is left to stand for 0.5h and discharged at 1C to 2.5V. First, the addition of fluorinated solvents improves the oxidation resistance of the electrolyte, thereby effectively improving the cycle performance of the battery. The cycle performance is further improved after the addition of TMSP and TMSB. The addition of FB does not have a significant effect on the cycle performance. LiODFB can effectively form a film at both the positive and negative electrodes, which can significantly inhibit the voltage drop during the first 10 cycles of the inhibitor battery, thereby improving the cycle performance of the battery.
[0058] Figure 4 The results of the battery high temperature storage test at 60°C are shown. The battery thickness is tested every 7 days, and the residual capacity of the battery is tested on the 28th day. Since the F element in the fluorinated solvent reacts with the water in the electrolyte to produce HF, thereby promoting the side reaction of the electrolyte, the addition of the fluorinated solvent will cause the battery to produce more gas and increase the thickness. The addition of silane additives reduces the water and free acid in the battery system, thereby further inhibiting the occurrence of electrolyte side reactions. The interfacial film generated by LiODFB passivates the positive and negative electrode surfaces, and can also inhibit the occurrence of gas production.
[0059] In addition, the dissolution of transition metals in the positive electrode material after 300 cycles was tested. The battery with 300 cycles was charged to 100% SOC, and the negative electrode sheet was removed after the battery was dissected. The negative electrode material powder was scraped for ICP testing, and the Mn element content was as follows: Figure 5 As shown. The addition of fluorinated solvents can improve the electrochemical stability of the battery system, thereby inhibiting the dissolution of transition metals. Silane additives TMSP and TMSB can further inhibit the dissolution of transition metals. FB has no significant effect on the dissolution of transition metals. The addition of film-forming additive LiODFB can also significantly inhibit the dissolution of transition metals.
[0060] In summary, the electrolyte of the present application, by adopting a solvent additive with a low HOMO energy level and optionally combining functional additives (acid and water removal and additives, fluorobenzene wetting additives, film-forming additives) to effectively improve the stability of the battery at high voltage, protect the electrolyte-electrode interface, inhibit the dissolution of transition metals, reduce the electrolyte side reactions caused by water, free acid and transition metals, improve the performance of the battery in high-temperature storage tests, and at the same time improve the cycle life and rate performance of the battery.
[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An electrolyte, characterized in that: It includes lithium salt, solvent and additive; the additive includes solvent additive; the solvent additive includes low HOMO energy level solvent; preferably, the low HOMO energy level solvent is 2,2,2-trifluoroethanol TFEA.
2. The electrolyte according to claim 1, characterized in that The mass proportion of the low HOMO energy level solvent in the electrolyte is 2-8%, preferably 8%.
3. The electrolyte according to claim 1, characterized in that The solvent additives also include acid and water removal additives; Preferably, the acid and water removal additive includes one or a mixture of tris(trimethylsilyl)phosphate TMSP or tris(trimethylsilyl)borate TMSB; Preferably, the acid and water removal additive accounts for 0.5-0.8% by mass in the electrolyte.
4. The electrolyte according to claim 1, characterized in that The acid and water removal additive is a mixture of tris(trimethylsilyl)phosphate TMSP and tris(trimethylsilyl)borate TMSB; preferably, the mass ratio of the two is 3:(3-5).
5. The electrolyte according to claim 1, characterized in that The solvent additive also includes a fluorobenzene wetting additive; Preferably, the fluorobenzene wetting additive is fluorobenzene FB; Preferably, the mass proportion of the fluorobenzene wetting additive in the electrolyte is 0.5-2%, preferably 1%.
6. The electrolyte according to claim 1, characterized in that The additives also include film-forming additives; Preferably, the film-forming additive is lithium difluorobis(oxalate)phosphate LiODFP; Preferably, the mass proportion of the lithium difluorobis(oxalate)phosphate LiODFP in the electrolyte is 0.2-1%, preferably 0.5%.
7. The electrolyte according to claim 1, characterized in that The solvent includes one or a mixture of carbonates, sulfates, sulfonates, fluoroesters, fluorosulfates, or fluorosulfonates; Preferably, the solvent includes one of propylene carbonate PC, ethylene carbonate EC, vinylene carbonate VC, ethyl methyl carbonate EMC, dimethyl carbonate DMC, diethyl carbonate DEC, fluoroethylene carbonate FEC, propylene sulfite PS, vinyl sulfate DTD, propenyl-1,3-sultone PST, and methylene methane disulfonate MMDS, or a mixture thereof; Preferably, the solvent is a mixture of propylene carbonate PC, ethyl methyl carbonate EMC, fluoroethylene carbonate FEC, and vinyl sulfate DTD; Preferably, the mass ratio of propylene carbonate PC, ethyl methyl carbonate EMC, fluoroethylene carbonate FEC and vinyl sulfate DTD in the electrolyte is: 6: (61.5-69.8): (5-8):
1.
8. The electrolyte according to claim 1, characterized in that The lithium salt is one or a mixture of LiPF6, LiBOB, LiBF4, LiODFB, LiTFSI, LiFSI, LiPO2F2, and LiFOP; Preferably, the lithium salt is a mixture of LiPF6, LiFSI and LiPO2F2; Preferably, the mass ratio of LiPF6, LiFSI and LiPO2F2 is 10:2:1.
2.
9. A semi-solid battery, characterized in that: The electrolyte comprising the electrolyte according to any one of claims 1 to 8.
10. The semi-solid-state battery according to claim 9, characterized in that: It comprises an electrolyte, a positive electrode sheet, a negative electrode sheet and a separator; the positive electrode active material in the positive electrode sheet is a lithium-rich manganese-based positive electrode material coated with a solid electrolyte.
Citation Information
Patent Citations
Bi-trifluoroethoxy bi-fluoride lithium borate salt, lithium ion battery low-temperature electrolyte comprising same and lithium ion battery
CN107565166A
Preparation method of amphiphilic fluoro-ether molecule and application of amphiphilic fluoro-ether molecule in lithium battery
CN116023239A
Novel liquid lithium ion battery additive
CN118054074A
Additive for nonaqueous electrolyte, nonaqueous electrolyte, and electricity storage device
WO2013005828A1
Cited By
Preparation method and application of water-resistant electrolyte for sodium-ion battery
CN119920981A